A Comparative Analysis of the Impact of Niger Delta Crisis on Edo and Delta States - Ehizoyanyan, Oaihimire Famous; Oke, Christiantus Ifeanyi Adebowale (UIN Sunan Gunung Djati Bandung, 2024)
The Niger Delta region of Nigeria has faced crises for over 40 years, resulting in high crime rates and increased insecurity of people, property, and investments. This study examines the impact of the regional crisis on the socioeconomic development and well-being of the inhabitants of Delta and Edo States. Employing quantitative research methods, including primary data collection instruments such as surveys and structured interviews, the study refined and codified the data for regression analysis. The findings reveal the detrimental effects of the Niger Delta crisis on the socioeconomic well-being of residents in both states, particularly in hindering access to essential needs such as clean water, quality education, and a healthy environment. Regression coefficients and modified coefficients of determination showed that residents of Delta State are more significantly affected by the crisis than those in Edo State. The study suggests enforcing international best practices in corporate social responsibility for oil and gas companies in the region. It also emphasizes the need for basic infrastructural development and adequate compensation and environmental remediation to achieve lasting peace and stability in the region.